2004
DOI: 10.1021/jo035634d
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Modes of Reactivity of Dialkyl Azodicarboxylates with P(III) Compounds:  Synthesis, Structure, and Reactivity of Products Other than the Morrison−Brunn−Huisgen Intermediate in a Mitsunobu-Type Reaction

Abstract: The reactivity of diethyl azodicarboxylate (DEAD)/diisopropyl azodicarboxylate (DIAD) with P(III) compounds bearing oxygen or nitrogen substituents is explored. Compounds with structures quite different from that of Morrison-Brunn-Huisgen intermediate R'(3)P(+)N(CO(2)R)N(-)(CO(2)R) (1), observed in the Mitsunobu reaction, have been established by using X-ray crystallography and NMR spectroscopy. Thus reactions with X(6-t-Bu-4-Me-C(6)H(2)O)(2)P-NH-t-Bu [X = S (8), CH(2) (9)] or XP(mu-N-t-Bu)(2)P-NH-t-Bu [X = Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Without this simple addition, the reaction could feasibly be simply occurring in the product vial that receives the reaction mixture, during the time taken to measure product radioactivity and prepare the sample for HPLC analysis. The active Mitsunobu intermediate formed is a Morrison‐Brunn‐Huisgen betaine, which will react with protic substrates: alcohols, amines, and carboxylic acids . Our own non‐radioactive experiments have confirmed that this betaine reacts with water forming the tri‐ n ‐butylphosphine oxide (PBu 3 O) and di‐ tert ‐butyl hydrazodiformate (DBAD‐H 2 ).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Without this simple addition, the reaction could feasibly be simply occurring in the product vial that receives the reaction mixture, during the time taken to measure product radioactivity and prepare the sample for HPLC analysis. The active Mitsunobu intermediate formed is a Morrison‐Brunn‐Huisgen betaine, which will react with protic substrates: alcohols, amines, and carboxylic acids . Our own non‐radioactive experiments have confirmed that this betaine reacts with water forming the tri‐ n ‐butylphosphine oxide (PBu 3 O) and di‐ tert ‐butyl hydrazodiformate (DBAD‐H 2 ).…”
Section: Resultsmentioning
confidence: 81%
“…The active Mitsunobu intermediate formed is a Morrison-Brunn-Huisgen betaine, which will react with protic substrates: alcohols, amines, and carboxylic acids. [33][34][35][36][37] Our own non-radioactive experiments have confirmed that this betaine reacts with water forming the tri-n-butylphosphine oxide (PBu 3 O) and di-tert-butyl hydrazodiformate (DBAD-H 2 ). Therefore, in the 11 C-urea synthesis, any remaining unreacted urea-forming betaine will react with the excess water (in the product vial) upon leaving the reaction loop, ensuring that the crude-HPLC is representative of the 11 C-labelled species formed inloop, not in-vial.…”
mentioning
confidence: 87%
“…In the case of aryl Products are known compounds. [14][15][16][17][18][19][20][21][22][23] iodides and activated aryl bromides, the reaction mixture was placed in a 1008C oil bath; and in the case of the less active and deactivated aryl bromides and chlorides, the reaction mixture was placed in a 1208C oil bath. After completion of the reaction, the catalyst was removed by centrifugation and the remaining mixture was extracted with ethyl acetate (3 Â 10 mL) and water several times and dried over anhydrous Na 2 SO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In all the above-performed reactions, the amount of palladium supported on SDPP was 0.001 g (0.5 mol-%). When the catalyst amount increased from 0.001 to 0.002 and 0.003 g, the reaction time decreased from 3 to 2 and 1 h, respectively (Table 1, entries 16,17). The effect of CuI on the reaction was also investigated.…”
Section: Catalytic Activity Of the Catalyst In C-c Coupling Reactionmentioning
confidence: 99%
“…The Mitsunobu DEAD phosphine betaine (Scheme 4) was never characterized by X-ray diffraction but af ew examples of its protonated form are known. [21] In contrast to the above,a fter addition of 1equiv of Et 2 O·HBF 4 to an acetonitrile solution of a1 :1 mixture of PEt 3 and compound 5, no color change was observed (Scheme 7). Proton NMR spectroscopy shows unchanged signals of 3,6-diphenyltetrazine and formationo fE t 3 PH + ,w hose acidic proton appearsa sad oublet at d = 5.8 ppm with al arge J H,P = 480 Hz; the 31 PNMR spectrum shows ap eak at d = 22.3 ppm, in agreement with the literature value.…”
Section: Tetrazinium Saltsmentioning
confidence: 90%